2018
DOI: 10.1111/jhn.12583
|View full text |Cite
|
Sign up to set email alerts
|

Different associations between body composition and alcohol when assessed by exposure frequency or by quantitative estimates of consumption

Abstract: Quantitative alcohol consumption and frequency of consumption were positively and inversely associated, respectively, with both BMI and WC among alcohol-consuming adults. Surveys are needed that evaluate both the quantity and frequency of consumption. The lowest BMI and WC were associated with a 'Mediterranean' drinking style (i.e. relatively little, but more frequently).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 33 publications
(60 reference statements)
1
18
1
1
Order By: Relevance
“…Additionally, a previous study combining cross-sectional and meta-analysis showed that spicy food intake frequency was positively associated with general obesity in rural Chinese populations 16. Both the BMI and waist circumference are considered as practical and effective indexes in evaluating obesity 24. BMI is closely related to body fat,25 and reflects the degree of obesity without the influence of differences in height.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a previous study combining cross-sectional and meta-analysis showed that spicy food intake frequency was positively associated with general obesity in rural Chinese populations 16. Both the BMI and waist circumference are considered as practical and effective indexes in evaluating obesity 24. BMI is closely related to body fat,25 and reflects the degree of obesity without the influence of differences in height.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, the extent of physical activity, alcohol intake, and concomitant disease influence the obesity/metabolic risk phenotypes [4,5,6,7,8]. However, few clinical studies have addressed the associations between obesity/metabolic risk phenotypes and dietary macronutrient intakes (carbohydrate, protein, and fat) [9], although several studies have found associations between macronutrient intakes and both obesity [10,11,12] and metabolic abnormalities [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The legend should at the very least contain a title for the table/figure and basic statistical information. Have a look at some published examples to see how this is done well .…”
Section: Writing the Resultsmentioning
confidence: 99%